LEGAL AID APPLICATION TO PREVENT SEXUAL VIOLENCE CRIMES IN MEDAN - Nasution, Rasina Padeni (Jurnal Meta-Yuridis, 2025)
This research aims to describe the application of patterns by legal aid institutions in preventing sexual violence crimes in Medan City using an empirical juridical research method. The results show that the implementation of the structural legal aid (BHS) pattern by LBH Medan and the structural gender legal aid (BHGS) pattern by LBH APIK are effective in providing legal protection by expanding access to justice for victims, focusing on recovery, and enhancing excellent services based on an equity approach. This approach not only focuses on resolving cases through legal channels but also seeks to transform unjust social structures resulting from power relations into more equitable social relations with a gender perspective. In conclusion, the implementation of BHS by LBH Medan and BHGS by LBH APIK plays a significant role in preventive and repressive efforts to prevent and address sexual violence in Medan City.